New Perspectives of Flipbook as Asynchronous English Reading Media - Masykuri, Edi Sunjayanto; Mezentse, Ivan; Nebolsina M.S, Nebolsina M.S; Anastasi, Nathalie; Bin Kamin, Yusri (JOLLT Journal of Languages and Language Teaching, 2024)
This purpose of the study was determining the students’ attitudes toward the use of flipbook as English reading media. The teacher met the problem to accelerate the studentâ€™s skills because of the uninteresting, difficult lesson. They do find the less of time to study in school. The findings of this study provided a comprehensive response to the following question: how do students feel about the use of flipbook as English reading media; How flipbook can increase the studentsâ€™ attention; and What are the challenges for student and teacher in education era 4.0.Â The mehod of the study was decriptive qualitative. The data was gathered by the researchers through the use of a questionnaire. In this study, there were twenty-seven students who were in their second semester junior high school. Case studies were the method of investigation for this project. In order to assess the data from the questionnaire, descriptive analysis was utilized. The findings of this study revealed that the students had a favorable opinion of flipbook as English reading materials. The average score on the questionnaire was 3.55, which places it in the "High" category when interpreted numerically. Some of these challenges were too large capacity, limited internet packages, and less supporting the old android.